2019
DOI: 10.1038/s41467-019-13257-4
|View full text |Cite
|
Sign up to set email alerts
|

Artificial spider silk from ion-doped and twisted core-sheath hydrogel fibres

Abstract: Spider silks show unique combinations of strength, toughness, extensibility, and energy absorption. To date, it has been difficult to obtain spider silk-like mechanical properties using non-protein approaches. Here, we report on an artificial spider silk produced by the water-evaporation-induced self-assembly of hydrogel fibre made from polyacrylic acid and silica nanoparticles. The artificial spider silk consists of hierarchical core-sheath structured hydrogel fibres, which are reinforced by ion doping and tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 47 publications
3
125
0
Order By: Relevance
“…Figure 1 presents the preparation process and interactions of the CDN-gel. The alkoxy groups are first hydrolyzed into silanol groups in the presence of water, and the silanol groups then condensate to form a siloxane bond [ 24 , 25 ]. The free-radical grafting polymerization mechanism of the PVA/PAA hydrogel triggered by visible light with a CQ initiator was proposed in our previous work [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 presents the preparation process and interactions of the CDN-gel. The alkoxy groups are first hydrolyzed into silanol groups in the presence of water, and the silanol groups then condensate to form a siloxane bond [ 24 , 25 ]. The free-radical grafting polymerization mechanism of the PVA/PAA hydrogel triggered by visible light with a CQ initiator was proposed in our previous work [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…1D conductive hydrogel microfibers could be the most important example of miniaturized hydrogels, whose fabrication are facing two main problems nevertheless: Dehydration versus conductivity: severe dehydration easily occurs as the fiber is spun in air, although a few researches have highlighted the significance of dehydration for enhancing the fiber strength and stretchability 11–13. There seems to be a trade‐off for bare hydrogel microfibers between fiber strength and ionic conductivity, which depend on adverse water contents.…”
Section: Introductionmentioning
confidence: 99%
“…To circumvent this issue, recently Ma et al reported a core–shell stretchable and conductive sodium polyacrylate hydrogel microfiber with a thin elastomer coating layer to prevent dehydration while maintaining good fiber elasticity 14. Nonetheless, the inert elastomer coating evitably leads hydrogel microfiber to be insensitive to environmental changes, which are unfavorable for sensing applications. Spinnability versus fiber strength: compared to electrospinning15,16 and extrusion spinning,9,10,17,18 microfluidic or draw‐spinning inspired from spider spinning procedure11–14,19,20 seems to be more suitable for fabricating long and uniform hydrogel microfibers. However, unless using the strategy of full dehydration, it is still challenging to compromise the spinnability and mechanical strength of hydrogel microfibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18] On the other hand, the high-water content in hydrogels leads to the liquidlike attributes of hydrogels, including permeability to a wide range of chemical and biological molecules, and transparency to optical and acoustic waves. [19][20][21][22] Moreover, the unique properties of hydrogels, such as its superior soness, wetness, responsiveness, biocompatibility, and bioactivity, indeed suggest the possibility of their crucial functions in cooling applications. 23,24 The heat absorption due to water content in hydrogels makes it a cooling device, [25][26][27][28][29] while water is abundant, non-corrosive, non-toxic, and non-ammable.…”
Section: Introductionmentioning
confidence: 99%